(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The article discusses the features of mixing ozone with treated water, directly in the technological pipeline. In connection with the significant volumes of water consumption in the interests of economic activity, the issue of disinfection of drinking water is acute. Along with traditional methods of disinfection, considerable attention of modern researchers is focused on the development of innovative technologies for this process. These include the technology of mixing the ozone-air mixture with treated water directly in the technological pipeline. The features of the formation and qualitative composition of the water of the Charvak reservoir were studied with an analysis of the reliability of the existing technology for the preparation of drinking water. The effect of ozone on the physical and chemical parameters of water taken from the reservoir was studied. The article discusses the process of disinfection of drinking water with ozone directly in the technological pipeline. A description is given of a model plant for disinfecting drinking water with ozone directly in the technological pipeline. The results of experimental studies on identifying the dependence of the degree of liquid disinfection with the help of ozone are presented. It has been established that the intensification of the process of ozone dissolution in water due to swirling flow is considered as the most economical and promising way to achieve 95-99% percent of ozone use. As a result of the study, a processing mode was determined that provides the smallest amount of ozone with maximum disinfection efficiency.